Strategi Komunikasi Niniak Mamak Dalam Mempertahankan Adat Larangan Tinggal Serumah Bagi Pengantin Baru Di Nagari Sungai Limau Kabupaten Dharmasraya - Dea Novika Sari; Tomi Hendra (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The Prohibition of Staying at Home for newlyweds is one of the customs in Nagari Sungai Limau which is still maintained today, this cannot be separated from Niniak Mamak's role as a traditional leader who tries to maintain traditions that have been used for generations. Thus, in this modern era, of course, a communication strategy is needed to maintain adat amidst the rise of educated nephews who migrate to various regions. Of course this is one of the obstacles experienced by Niniak Mamak in maintaining the custom of not living in the same house for newlyweds. The type of research used is a type of field research with a qualitative descriptive approach, the data collection method used is observation by means of which researchers see directly field activities, interviews by appointing several sources needed in data collection, and documentation in the form of files/data obtained from the Guardian's Office Nagari Sungai Limau. The results showed that Niniak Mamak's Communication Strategy in Maintaining the Customary Prohibition of Staying at Home for Newlyweds in Nagari Sungai Limau, can be proven by the habits that are applied at every celebration of Idhul Fitri with the strategy of gathering all the children of nephews at the Nurul Huda Nagari Sungai Limau Mosque, then Niniak Mamak will give directions to her nephews regarding customs including the Prohibition of Staying at Home for Newlyweds, during the event the nephew's children may only listen without being allowed to speak. And also Niniak mamak did the Sitting Mamak activity before holding the marriage contract for her nephew's children to provide directions and information related to the Customary Prohibition of Staying at Home for Newlyweds.